(untitled) (Fiep Bulletin - online, 2014)
Faced with symptoms caused by cervicobrachialgias as pain, paresthesia and muscle weakness, it was investigated whether the technique of neural mobilization is effective for patients with cervicobrachialgias, recovering both the mechanical and physiological function of the nervous system. It was performed a double-blind study, qualitative-quantitative type, cause-effect, slitting longitudinal. The sample consisted of 10 patients, selected from the inclusion and exclusion criteria, which was first performed an initial evaluation, followed by the application of the technique of neural mobilization of the median and radial nerve, for ten minutes each, in the upper limb symptoms. It had as parameters of improves the evolution of pain analyzed by Visual Analog Scale of pain and evolution of the range of motion of the cervical spine, measured by the inclinometer cervical (CROM), and upper limb measured by digital inclinometer Baseline. After data collection was performed t-student test for comparison of dependent average on the 5% level of probability. It was noted significant improvement in all measure of range motion, the largest gain in the cervical spine was rotation (83%), and adduction (30%) for the upper limb and significant improvement of pain present. It is concluded that neural mobilization is effective in reducing the painful and evolution of both range of motion from cervical spine and upper limb symptoms, defined within the sample.